2016
DOI: 10.1038/aps.2016.21
|View full text |Cite
|
Sign up to set email alerts
|

Metformin exerts glucose-lowering action in high-fat fed mice via attenuating endotoxemia and enhancing insulin signaling

Abstract: Aim: Accumulating evidence shows that lipopolysaccharides (LPS) derived from gut gram-negative bacteria can be absorbed, leading to endotoxemia that triggers systemic inflammation and insulin resistance. In this study we examined whether metformin attenuated endotoxemia, thus improving insulin signaling in high-fat diet fed mice. Methods: Mice were fed a high-fat diet for 18 weeks to induce insulin resistance. One group of the mice was treated with oral metformin (100 mg·kg -1 ·d -1 ) for 4 weeks. Another grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 42 publications
8
61
1
Order By: Relevance
“…Previous studies have consistently shown that high-fat diet significantly reduced A. muciniphila abundance in different animal models (Anhê et al, 2015; Axling et al, 2012; Everard et al, 2013; Li et al, 2016; Roopchand et al, 2015; Zhou et al, 2016). A treatment of high-fat diet (60% fat) for as short as 8 weeks on DIO mice led to a 100-fold decrease of A. muciniphila (Everard et al, 2013).…”
Section: High Fat Diet and Alcohol Could Reduce Abundance Of A Mmentioning
confidence: 84%
See 2 more Smart Citations
“…Previous studies have consistently shown that high-fat diet significantly reduced A. muciniphila abundance in different animal models (Anhê et al, 2015; Axling et al, 2012; Everard et al, 2013; Li et al, 2016; Roopchand et al, 2015; Zhou et al, 2016). A treatment of high-fat diet (60% fat) for as short as 8 weeks on DIO mice led to a 100-fold decrease of A. muciniphila (Everard et al, 2013).…”
Section: High Fat Diet and Alcohol Could Reduce Abundance Of A Mmentioning
confidence: 84%
“…A muciniphila ) play an important role mediating metformin activity. Further, exogenous LPS administration (subcutaneous injection, 50 μg/kg/day for 5 days) nearly completely blocked all these beneficial effects of metformin on glucose metabolism, insulin signaling and redox status in the mice (Zhou et al, 2016), indicating that LPS also plays an essential role in mediating metformin activity. Previous studies also consistently showed that A. muciniphila administration significantly reduced serum LPS levels (Everard et al, 2013; Li et al, 2016).…”
Section: Metformin Consistently Increased a Muciniphila Abundancementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the widely used diabetes drug metformin may help mitigate gut dysbiosis associated with obesity and diabetes. In human [55, 56] and mice [42•, 5759] studies, metformin has been positively associated with the relative abundance of A. muciniphila and short chain fatty acid-producing bacteria in the gut microbiota. Based on this small but growing literature base, it is tempting to postulate that metformin—a drug with no known risks for the mother or fetus—could not only help ameliorate diabetes-associated dysbiosis in pregnancy, but also reduce transmission of diabesogenic bacteria to the newborn.…”
Section: Maternal Microbiome and Metabolic Disorders In Pregnancy: Pomentioning
confidence: 99%
“…Numerous studies using the AMPK-activator, Metformin, squarely implicate the AMPK-dependent stress polarity pathway as a major therapeutic target in these metabolic disorders [79-81]. Metformin administration enhances gut barrier integrity, attenuates endotoxemia and enhances insulin signaling in high-fat fed mice, which accounts for the beneficial effects of metformin on glucose metabolism, enhanced metabolic insulin response, and reduced oxidative stress in liver and muscle of the mice [79].…”
Section: Pathophysiologic Implications Of the Ampk-giv Stress Signalimentioning
confidence: 99%